Prevalence of External and Internal Parasites and their Effects on Body Performance to Local Chickens in Erbil City - Azeez, Bakhtyiar Shwan; Yassin, Ayshan Rafat (Diyala Journal for Veterinary Sciences, 2024)
The parasites are known to infect local chickens and are one of the genuine issues leading to economic loss in breeding farms and rural regions that grow chickens yearly. This study aims to know the prevalence of external and internal parasites and their effects on body performance in local chickens in Erbil city. The research was carried out on 500 different species of local chickens to investigate the existence of external and internal parasites and their prevalence in the Erbil city region of Kurdistan/Iraq from October 2022 to January 2023. Overall findings showed that 280 out of 500 hens evaluated (56%) had external parasite infestations; out of that, 95 % (475/500) were infested with lice, and 5% (25/500) of it with the larval stage of soft tick. However, of the 500 hens that were tested, 13% (65/500) had internal parasite infections, including cestode which made up 65% (45/65), and nematodes, which made up 31% (20/65). This study revealed that 56% of local chickens were infested with external parasites, the majority of which were lice (95%). Internal parasites were found to be more prevalent in 65% of cestode species, nematode species had a lower frequency of 31% in Erbil city.